(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2022)
Incessant usage of fossil fuel (non renewable natural resources) is rapidly diminishing, & ir combustion is causing intensification in carbon dioxide in atmosphere. For ecological & economical sustainability, renewable carbon-neutral transportation fuels are needed. Biodiesel made from oil crops has potential to be a carbon neutral sustainable substitute to petroleum-based fuels. It’s mainly generated via direct usage & mixing, micro emulsions, rmal cracking (pyrolysis), & transesterification, & is fabricated of mono alkyl esters of long-chain fatty acids. Transesterification of vegetationoils & animal fats is most prevalent technique for producing biodiesel. Batch procedures, supercritical processes, ultrasonic techniques, & microwave methods are all accessible for trans esterification reaction. Liquid content of oils or fats & free fatty acids, reaction duration, & reaction temperature are all variables that affect transesterification process. significance, history, characteristics, suppliers, & methods for producing biodiesel are discussed in this study.